Genomic surveillance of Rift Valley fever virus - Juma, John; Limbaso, S.K. (ILRI, 2024)
Pathogen genomic data are critical in the development of vaccines and diagnostics. Currently, there are only a handful of Rift Valley fever virus (RVFV) genomic sequence data.